2008
DOI: 10.1124/mol.107.043406
|View full text |Cite
|
Sign up to set email alerts
|

Primary Peripheral T Cells Become Susceptible to 2,3,7,8-Tetrachlorodibenzo-p-Dioxin-Mediated Apoptosis in Vitro upon Activation and in the Presence of Dendritic Cells

Abstract: Although the toxic effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) on T cells in vivo have been well characterized, attempts to reproduce these findings in vitro have not been successful. In the current study, we examined whether activation or the presence of dendritic cells (DCs) would make primary naive T cells from C57BL/6 mice susceptible to TCDD-induced apoptosis in vitro. Although nonactivated primary T cells cultured with 10 to 1000 nM TCDD were relatively resistant to apoptosis, they became sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 45 publications
4
48
0
1
Order By: Relevance
“…Previous studies have implicated the Ahr pathway in the generation of TH17ϩ inflammatory cells (50,51). Furthermore, several reports have shown that T cells in the thymus and periphery are highly sensitive to TCDD-induced apoptosis (47,48,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have implicated the Ahr pathway in the generation of TH17ϩ inflammatory cells (50,51). Furthermore, several reports have shown that T cells in the thymus and periphery are highly sensitive to TCDD-induced apoptosis (47,48,52).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TCDD induces apoptosis in T cells involving Fas/FasL interactions (48). We investigated whether the increased susceptibility of activated E2F2 Ϫ/Ϫ ; three independent experiments).…”
Section: Aberrant Cytosolic Accumulation Of Ahr Pathway Proteins In Amentioning
confidence: 99%
“…PCR was performed using mouse FasL-or Fas-specific sets of forward and reverse primers as described earlier (Singh et al, 2008). The PCR products, generated from mouse Fas and FasL primer pairs, were normalized against mouse-specific 18S PCR products as described previously (Singh et al, 2008). The intensity of PCR products was determined using the ChemiDoc image analysis system (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, single cell suspension of thymic cells post-VEH or post-DES treatment was prepared as described above. Expression of Fas and FasL was determined by RT-PCR as described previously (Singh et al, 2008). For RT-PCR, total RNAs from VEH-or DES-treated groups were isolated using the RNeasy mini kit following the protocol of the company (QIAGEN, Germantown, MD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation